Stochastic Radiation Model for Cable Bundle with Random Wires - Jia, Jin; Lai, Zhida; Lei, Jianmei; Wang, Quandi (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Cable bundle is often the main radiation structure due to its length in automotive electrical or electronic systems. Random wire positions in a cable bundle is a challenge for the modeling in perspective of Electromagnetic Compatibility (EMC). This work addresses the uncertainty property of a cable bundle due to its random wire positions, through a stochastic-model approach. Random wire position distributions in a bundle adopt Gaussian norm. A spline interpolate function is used to improve the continuity of wires along the bundle. To calculate the common-mode (CM) current on the bundle, the composed non-uniform wires are modeled by cascaded uniform segments or Chebyshev Expansion Method based smooth lines. Further CM current based bundle radiation is calculated using electric-dipole model. Proposed modeling methodology is assessed by comparing CM current and radiation predictions versus measurement data and theoretical results. Predictions agree well with measurements especially in statistics.